Antiepileptic Drug Disposition in Pregnancy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the Karolinska Institute, Stockholm, Sweden; and centers in Oslo, Norway, and Milan, Italy, reviewed the literature on gestational effects on pharmacokinetics of older and newer antiepileptic drugs (AEDs).